0.5 V, 5 MHz active-RC biquad filter in 90 nm CMOS technology. (2016) - Rekha, S.; Laxminidhi, T.
This paper proposes a low voltage, low power active-RC biquad filter operating on a power supply voltage of 0.5 V in 90 nm standard CMOS technology. A CMOS inverter-based transconductor is used as the building block. A sub-threshold model is developed for the transconductor as the transistors are operating in sub-threshold region. A feed-forward compensated OTA is designed using this transconductor and is used to realise the filter. OTA exhibits an open loop DC gain of 61.89 dB and a unity gain bandwidth of 1.35 GHz. It is stable with a phase margin of 52.85°. Power consumed by the OTA is as low as 29.91 µW. The designed filter has a cut-off frequency of 5 MHz and offers a dynamic range of 55.78 dB with a figure of merit of 0.022 fJ. Power consumed by the filter is 58.76 µW.